THE USE OF SILICONE KEY AND METER CONVERGENCE ANGLE OF THE TOOTH TO CONTROL THE ACCURACY OF THE TOOTH PREPARATION FOR METAL-CERAMIC CROWNS - He Zhiqiang; Qin Lingfeng (Український стоматологічний альманах)
Relevance of the topic. Technology for manufacturing metal-ceramic crowns and bridges provides special training abutment teeth, which differs substantially from that in the manufacture of other types of fixed structures. Accuracy of preparation, strict observance of the sequence and content of clinical and laboratory stages in the future provides a good retention of the prosthesis and high aesthetic appearance. To determine the depth of the preparation of dental hard tissues several methods. One involves applying a predetermined amount of marking grooves on the surface of the labial and lingual as well as in the neck of the tooth and the cutting edge. Several authors for this purpose use silicone key. Both methods only regulate the depth of preparation of dental hard tissues and did not allow to take into account the value of the bevel approximal surfaces, so-called angle of convergence. As you know, it depends on the type of prosthesis and group membership teeth. In the manufacture of single metal crowns it is for the front teeth 5 to 7 degrees, and to the side, - 7 to 12 degrees. Unfortunately, the doctor without the use of a special device, visually, is not able to accurately determine the value of convergence of interproximal tooth stump walls.